Annotation of Fusarium graminearum (PH-1) Version 5.0 - King, Robert (Genome Announc, 2017)
Fusarium graminearum floral infections are a major risk to the global supply of safe cereal grains. We report updates to the PH-1 reference genome and significant improvements to the annotation. Changes include introduction of legacy annotation identifiers, new gene models, secretome and effectorP predictions, and inclusion of extensive untranslated region (UTR) annotations.